The general analysis of the key performance indicators of medical institutions of Ukraine - Трофименко, Ганна Сергіївна (Technology audit and production reserves, 2012)
The article describes the results of the analysis of the key performance indicators of medical institutions of Ukraine. The conclusions about the feasibility of such indicators in comparison dynamics for several years